PERBEDAAN HASIL BELAJAR MATERI IKATAN KIMIA MENGGUNAKAN MEDIA KOMIK MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE TAI DAN STAD DI SMA KELAS X - Yopita Sari Sihombing; Jasmidi Jasmidi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2022)
The Purpose of this study aims to determine differences in learning outcomes using media comics through cooperative learning model type TAI and cooperative type STAD on the material of Chemical Bonds and knowing the differences in interest in learning with models TAI type cooperative learning on Bond material Chemistry. The population in this study were all students of class X IPA in SMA Private Harapan Medan, which consists of three classes. The sample used in this study; two classes were taken using the purposive sampling technique. The instrument with 20 questions that are valid and reliable. Learning outcomes data in te Normality tes with a value of sig.0,06 and 0,00 (0,05) means that the learning outcomes data are normally distributed. Test the homogeneity of the result data learning 0,603 0,05, it can be concluded that the variance of learning outcomes data on Experiments 1 and 2 are homogeneous. Hypothesis testing was carried out with Two Sample, the learning outcomes (2-tailed) 0,080(0,05) and student interest (2-tailed) 0,65(0,05) so that Ha is accepted and HO is rejected, it can be concluded that there is Differences in student learning outcomes between those who are taught using the model TAI and STAD cooperative learning with what is taught by comics media at the subjects of the Chemical Association and there are differences in student learning interests between students those who are taught use the TAI cooperative learning model and STAD with what comic media teaches on the subject of the Chemical Association. By therefore the TAI and STAD type cooperative learning models with comic media on chemically bonded material are suitable for use.Keywords : Cooperative Learning Model Type Team Assisted Individualization ( TAI) and Students Teams Achievement Division (STAD), Media comics, learning outcomes, interest in learning, chemical bonds